2023
DOI: 10.1002/uog.26291
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hypertensive disorders after screening at 36 weeks' gestation: comparison of angiogenic markers with competing‐risks model

Abstract: ObjectiveTo compare the performance at 35+0 to 36+6 weeks’ gestation of screening for delivery with pre‐eclampsia (PE) at various time points, using one of three approaches: placental growth factor (PlGF) concentration, the soluble fms‐like tyrosine kinase‐1 (sFLT‐1) to PlGF concentration ratio, or the competing risks model, which combines maternal risk factors with biomarkers to estimate patient‐specific risk.MethodsThis was a prospective observational study in women attending for a routine hospital visit at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Screening for term PE is best performed at 35 + 0 to 36 + 6 weeks' gestation by a combination of maternal factors, MAP, PlGF and serum soluble fms-like tyrosine kinase-1, which can identify approximately 70% of subsequent disease 26,27 . The rationale for such late third-trimester screening is identification of a high-risk group that would benefit from close monitoring to minimize adverse perinatal events for those that develop PE, by determining the appropriate time and place for delivery.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Screening for term PE is best performed at 35 + 0 to 36 + 6 weeks' gestation by a combination of maternal factors, MAP, PlGF and serum soluble fms-like tyrosine kinase-1, which can identify approximately 70% of subsequent disease 26,27 . The rationale for such late third-trimester screening is identification of a high-risk group that would benefit from close monitoring to minimize adverse perinatal events for those that develop PE, by determining the appropriate time and place for delivery.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…In a recent study, we suggested that GlyFn is a potentially useful first‐trimester biomarker for preterm PE 21 . We have also reported that prediction of term PE is achieved by screening at 35–37 weeks' gestation by a combination of maternal risk factors with MAP, PlGF and sFlt‐1, with a detection rate for term PE of about 70% at a screen‐positive rate of 10% 22–24 .…”
Section: Discussionmentioning
confidence: 95%
“…We have demonstrated previously the value of screening for preterm PE at 11-13 weeks' gestation and screening for term PE at 35-37 weeks with use of the competing-risks approach; essentially, information from maternal demographic characteristics and medical history are combined with multiples of the median values of biomarkers, adjusted for maternal factors, to provide accurate and reproducible personalized assessment of risks [19][20][21][22][23][24][25][26] . We have also advocated that the same approach be used in the prediction of imminent PE in women presenting to specialist clinics with some signs and/or symptoms of hypertensive disorder [24][25][26] . We suggested that use of cut-offs in measured biomarkers or their ratio to define clinical management has the advantage of simplicity.…”
Section: Interpretation Of Results and Implications For Clinical Prac...mentioning
confidence: 99%
“…Treatment of the high-risk group with aspirin (150 mg/day from 12 to 36 weeks) reduces the rates of early and preterm PE by about 90% and 60%, respectively 5 . The second strategy involves assessment of risk at 36 weeks' gestation by a combination of maternal risk factors with MAP, PlGF and soluble fms-like tyrosine kinase-1 (sFlt-1) (third-trimester triple test), and has a detection rate for term PE with delivery at ≥ 37 weeks of about 70%, at a screen-positive rate of 10% [6][7][8] . A randomized trial is currently evaluating timed birth based on personalized risk of PE, a strategy that has the potential to decrease the rate of term PE by about 60% 9 .…”
Section: Introductionmentioning
confidence: 99%